Timing and Origins of Local and Distant Metastases in Lung Cancer - Tang, Wen-Fang; Wu, Min; Bao, Hua; Xu, Yang; Lin, Jie-Shan; Liang, Yi; Zhang, Yu; Chu, Xiang-Peng; Qiu, Zhen-Bin; Su, Jian; Zhang, Jia-Tao; Zhang, Chao; et al. (Journal of thoracic oncology, 2021)
Metastasis is the primary cause of lung cancer-related death. Nevertheless, the underlying molecular mechanisms and evolutionary patterns of lung cancer metastases are still elusive. We performed whole-exome sequencing for 40 primary tumors (PTs) and 61 metastases from 47 patients with lung cancer, of which 40 patients had paired PTs and metastases. The PT-metastasis genomic divergence, metastatic drivers, timing of metastatic dissemination, and evolutionary origins were analyzed using appropriate statistical tools and mathematical models. There were various degrees of genomic heterogeneity when comparing the paired primary and metastatic lesions or comparing metastases of different sites. Multiple metastasis-selected/enriched genetic alterations were found, such as MYC amplification, NKX2-1 amplification, RICTOR amplification, arm 20p gain, and arm 11p loss, and these results were were also featured in a meta-analysis cross-validated using an independent cohort from Memorial Sloan-Kettering Cancer Center database. To elucidate the metastatic seeding time, we applied a metastatic model and found 61.1% of the tumors were late dissemination, in which the metastatic seeding happened approximately 2.74 years before clinical detection. One exception was lymph node metastases whose dissemination time was relatively early. By analyzing the evolutionary origins, we reported that nonlymph node metastases were mainly seeded by the PT (87.5%) rather than the earlier colonized lymph node metastases. Our results shed light on the molecular features that potentially drive lung cancer metastases. The distinct temporospatial pattern of disease progression revealed that lung cancer was susceptible to either late dissemination or indolent early lymph node metastases, leaving a potential time window to minimize metastases by early cancer detection.